Efisiensi mesin pemecah batu split (stone crusher) dan pengaruhnya terhadap kerugian (losses) produksi - Kaspul Anuar; Syafri Syafri; Mia Nur Kholizah (Universitas Muhammadiyah Metro, 2023)
Generally, cement factories produce secondary product in the form of split stone. Split stone products are produced from basalt rock crashed into aggregates of a certain size. This research is based on the results of split stone production, which is not following the target at a cement factory on the island of Sumatra. It creates production losses and financial losses. One of the causes of the incompatibility of the split stone production target is the non-optimal performance of the stone crusher machine. This research conducted a study related to the calculation of the stone crusher machine efficiency. Data in the real production capacity was obtained from recorded data in the field for twelve months. From the data obtained, the highest efficiency of the stone crusher machine of 58.32% occurred in the first month with a total production loss of 1,086 tons or equivalent to Rp. 217,296,000. The lowest efficiency of the stone crusher of 3.52% occurred in the eighth month with a total production loss of 12,133 tons or equivalent to Rp 4,478,112,000.